The communication of the tourist destinations: conceptual and theoretical approaches to the definition of a state of the art (Andamios, Revista de Investigación Social, 2012)
This paper aims to highlight the changes experienced by the communication register of tourist destinations in the last ten years. The possibilities offered by Information Technology and Communication (CIT), in line with a renewed use of the communication strategy, notes the  need to define a new state of the art for the binomial ‘communication and tourism’. Indeed, the use of merely informative and/or promotional supports has evolved into a new logic of production, own the corporate level, putting the tourists in the core of the communication strategy. In this respect, the terms ‘persuasion’ and ‘emotion’ define the new coordinates of work for the communication of the tourist destinations.
Keywords: Communication; tourism; tourist destination; branding; emotion